2018
DOI: 10.1371/journal.pgen.1007350
|View full text |Cite
|
Sign up to set email alerts
|

Transcription and translation of the sigG gene is tuned for proper execution of the switch from early to late gene expression in the developing Bacillus subtilis spore

Abstract: A cascade of alternative sigma factors directs developmental gene expression during spore formation by the bacterium Bacillus subtilis. As the spore develops, a tightly regulated switch occurs in which the early-acting sigma factor σF is replaced by the late-acting sigma factor σG. The gene encoding σG (sigG) is transcribed by σF and by σG itself in an autoregulatory loop; yet σG activity is not detected until σF-dependent gene expression is complete. This separation in σF and σG activities has been suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…2016). Because of the autoregulatory nature of σ G , several mechanisms concur with inhibition by CsfB to prevent its premature activity (Mearls et al. 2018).…”
Section: Resultsmentioning
confidence: 99%
“…2016). Because of the autoregulatory nature of σ G , several mechanisms concur with inhibition by CsfB to prevent its premature activity (Mearls et al. 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Regulation of translation initiation via SD-sequestration is an old theme that initially started with the study of bacteriophage genes (de Smit and van Duin, 1990) and ribosomal proteins (for a review see Duval et al, 2015). More recently, its impact on other bacterial genes such as sigma factors (Mearls et al, 2018) and translational riboswitches (Rinaldi et al, 2016) has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Why then does σ G fail to become fully active in spoIIQ and spoIIIA mutants? The transmembrane segment of SpoIIQ regulates expression of the gene for the anti-σ G factor CsfB (Flanagan et al, 2016) and several features of the sigG promoter, mRNA leader sequence, and start codon dampen expression (Mearls et al, 2018), but these findings do not explain a more general requirement of SpoIIQ and…”
Section: Atp Does Not Appear To Be the Limiting Factor For Postengumentioning
confidence: 93%
“…Activity of σ F initiates a signaling pathway that leads to proteolytic activation of Pro‐σ E in the MC (Konovalova et al ., 2014). During the ensuing engulfment process, σ F activity produces SpoIIQ, which inserts in the inner FS membrane, and σ E activity produces SpoIIIA proteins, which insert in the engulfing MC membrane (Figure 1, left side), forming channels between the two compartments that are required for full activity of σ G in the FS and maintenance of FS integrity (Blaylock et al ., 2004; Doan et al ., 2005; 2009; Camp and Losick, 2008; 2009; Meisner et al ., 2008; Mearls et al ., 2018). The activation of σ G coincides with completion of engulfment and initiates a signaling pathway that leads to proteolytic cleavage of Pro‐σ K to active σ K in the MC (Kroos and Akiyama, 2013; Konovalova et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation